Optimisation algorithms for the cooperative communication problem in mobile ad–hoc networks. (18th June 2012) - Jang, Kil–Woong
In this paper, we propose efficient optimisation algorithms to obtain a set of routes to maximise the connectivity among the mobile nodes for the Cooperative Communication Problem (CCP) in mobile ad–hoc networks. We solve the CCP by using heuristic approaches that can efficiently obtain high–quality solutions within a reasonable time for a large–size network. We evaluate and compared these algorithms with other existing algorithms in terms of the number of connections and the computation time of the algorithms. The comparison results show that the proposed algorithms outperform other existing algorithms and can efficiently solve the CCP in mobile ad–hoc networks.